Aquatic Insect Diversity as Bioindicators of Water Quality in Organic Inorganic Rice Fields, Pringsewu, Lampung: Keanekaragaman Serangga Air sebagai Indikator Kualitas Air di Sawah Organik Anorganik di Pringsewu Lampung - Pramudita, Rima; Dania Pratami, Gina; Meidaliyantisyah; Handayani, Kusuma (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2025)
The diversity of aquatic insects serves as an important indicator for assessing the quality of agricultural ecosystems, particularly in organic and conventional (non-organic) rice fields. Organic farming, which relies on natural inputs, tends to support greater biodiversity, whereas conventional farming may reduce it due to the use of chemical substances. This study aimed to examine the diversity, dominance, evenness, and environmental factors influencing the presence of aquatic insects in two types of agricultural systems in Tulung Agung Village, Lampung. The results showed that the organic rice fields had higher aquatic insect diversity, with a diversity index (H') of 2.3386, a dominance index (D) of 0.058, and an evenness index (E) of 0.9411. In contrast, the conventional rice fields showed a diversity index (H') of 0.9743, a dominance index (D) of 0.5188, and an evenness index (E) of 0.3312. Environmental factors had no significant effect on aquatic insects in the organic fields, but showed a strong correlation in the conventional fields, with a correlation value (r) of 0.905 and a significance value (p) of 0.035. These findings highlight that organic farming systems are better able to support a more stable aquatic ecosystem balance.